2011
DOI: 10.1007/s12272-011-0210-4
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the F-actin cytoskeleton and monolayer barrier integrity induced by PAF and the protective effect of ITF on intestinal epithelium

Abstract: To explore whether platelet-activating factor (PAF) can disrupt the intestinal epithelial barrier directly and is associated with structural alterations of the F-actin-based cytoskeleton, and to observe the protective effect of intestinal trefoil factor (ITF), we establish an intestinal epithelia barrier model using Caco-2 cells in vitro. Transepithelial electrical resistance and unidirectional flux of lucifer yellow were measured to evaluate barrier permeability; immunofluorescent staining and flow cytometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…28 F-actin and tight junction disruption has also been seen in intestinal epithelial cells. 29 We also observed that long-term PAF treatment (greater than 24 hours) reduced tight junction integrity. Although these responses are reversible by PAFR antagonists, such treatment may not be necessary as these exposures are longer than any intended in vitro or in vivo use.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…28 F-actin and tight junction disruption has also been seen in intestinal epithelial cells. 29 We also observed that long-term PAF treatment (greater than 24 hours) reduced tight junction integrity. Although these responses are reversible by PAFR antagonists, such treatment may not be necessary as these exposures are longer than any intended in vitro or in vivo use.…”
Section: Discussionsupporting
confidence: 55%
“…As a mediator of inflammation, PAFR activation can alter tight junction integrity in endothelial and intestinal epithelial cells. 28,29 We examined the effects of PAF on tight junction integrity in airway epithelia. PAF application to the apical and basolateral surfaces of HAE for 8 hours caused no alteration of tight junction morphology as assessed by ZO-1 immunostaining.…”
Section: Resultsmentioning
confidence: 99%
“…The transition from fibers traversing through the cytoplasm to their localization to the cell periphery is the possible consequence of the mechanochemical stress imposed by the particles onto the epithelial membrane [25]. Similar structural alterations of f-actin cytoskeleton, leading to its condensation in pericellular bands, have been previously observed under the effect of substances that disrupt the intestinal epithelial barrier [26]. In general, the cytoskeletal pattern of actin molecules in the perijunctional region of intestinal epithelial cells tends to be either disrupted and modulated [27], or thickened and tightened [28] following incubation with particles or enteric biomolecules.…”
Section: Resultsmentioning
confidence: 80%
“…Similarly, all TFF peptides were shown in vitro in premalignant colonic epithelial cells to require activated Src/RhoA to induce cellular invasion (86, 87). Further support of TFF-mediated actin cytoskeleton rearrangement was demonstrated in the Caco-2 cells by Xu et al (88), who showed that TFF3 was capable of restricting platelet-activating factor-induced disruption of the F-actin cytoskeleton. These studies point to the role of TFF in activating actin cytoskeleton changes during cell migration.…”
Section: Trefoil Factor Peptides and Cell Migrationmentioning
confidence: 80%